Kyrgyz Republic : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2004)
This paper on the Poverty Reduction Strategy Papers (PRSPs) on the Kyrgyz Republic explains macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major sources of financing. Partnerships developed by the Kyrgyz Republic with all representatives of the donor community became an important factor in raising the level of coordination and effectiveness of foreign aid. Promotion and further development of the potential of government and nongovernment organizations and local communities on the joint development and implementation of the development programs remain an important task.